Who supports the African Union? Understanding the determinants of citizens' opinion for African integration - Simplice Asongu; Samba Diop; Cheikh Tidiane Ndiaye (African Governance and Development Institute (AGDI), 2024)
The objective of the paper is to investigate the legitimacy of the African Union by examining the socio-demographic determinants of citizens' support of African integration. To do this, we use Rounds 4, 5, 6 and 8 of the Afrobarometer survey data corresponding to more than 110 000 respondents. Using logistics regressions, we find that individual characteristics such as living area, education, employment status, political membership, freedom, living condition and Living Poverty Index (LPI) are significantly related to the probability of supporting African integration. The findings are largely robust to dynamics of regional integration, the African Union and Regional Economic Communities (RECs). Thus, since African citizens' trust in the unification could be considered as a condition of legitimacy in the process, our results suggest that more efforts should be done to gain credibility, especially as it pertains to the benefits of African integration.
Keywords: C23; O55; 330; Institutional support; Afrobarometer survey; African Union